Development of an Animaker-Based Animated Learning Video to Enhance Seventh-Grade Students’ Mathematical Conceptual Understanding of One-Variable Linear Equations and Inequalities - Meilatul Zuhro; Jefri Marzal; Mujahidawat (Sakura Digital Nusantara, 2026)
This study developed an Animaker-based animated learning video to support seventh-grade students’ mathematical conceptual understanding of one-variable linear equations and inequalities. The study used a research and development approach guided by the Analyze, Design, Develop, Implement, and Evaluate (ADDIE) framework. Needs analysis, expert review, individual teacher appraisal, small-group testing, and field implementation were conducted at State Islamic Junior High School (Madrasah Tsanawiyah Negeri/MTsN) 4 Merangin. Two university lecturers reviewed the media, content, and assessment instruments; one mathematics teacher, eight students in the small-group trial, and 30 students in the field implementation evaluated usability. The final product comprised curriculum-aligned animated explanations, worked examples, guided pauses, and practice prompts. Expert review classified the product and instruments as valid after revision. Practicality scores were 3.78 from the teacher, 4.12 from the small group, and 4.15 from the field group on a five-point scale. Students’ mean conceptual-understanding score increased from 10.867 on the pre-test to 18.200 on the post-test, with a normalized gain of 0.67 (moderate). Students’ predominant perception category was agree. The product is a feasible digital-learning resource for concept-focused mathematics instruction, while broader controlled evaluations are needed to establish comparative effectiveness.